Do Intergroup Threats Provoke Intergroup Anxiety? An Experimental Study on Chinese Ethnic Group in Indonesia - Gabrielle Irene; Sutarimah Ampuni (Jurnal Psikologi Sosial, 2020)
Through an online experiment, this study examines the role of intergroup threat on intergroup anxiety in Indonesian Chinese ethnic group, by considering the moderating role of positive intergroup contact. The posttest-only randomized experimental design was used in this study. Sixtyfour Chinese Indonesian college students (male = 31, female = 33) were randomly assigned into treatment group (male = 14, female = 18) and control group (male = 17, female= 15). All participants were first asked to complete a positive intergroup contact scale. Following this, participants in the treatment group were asked to read threat-inducing reading passages, while those in the control group were given neutral reading passages. They then were asked to complete a manipulation check and intergroup anxiety scale. Data were analyzed using analysis of covariance (ANCOVA). Results showed that when positive intergroup contact was controlled, intergroup threat significantly affected intergroup anxiety but in the direction opposing the hypothesis. Instead of showing higher intergroup anxiety, the experimental group showed lower intergroup anxiety compared to the control group. An interview on a few participants was conducted to explore possible explanations of this result.